Nuclear Factor Erythroid 2-Related Factor 2 and SARS-CoV-2 Infection Risk in COVID-19-Vaccinated Hospital Nurses - Stefano Rizza; Luca Coppeta; Gianluigi Ferrazza; Alessandro Nucera; Maria Postorino; Andrea Quatrana; Cristiana Ferrari; Rossella Menghini; Susanna Longo; Andrea Magrini; Massimo Federici (Vaccines)
Background/Objectives: The COVID-19 pandemic has caused sickness and death among many health care workers. However, the apparent resistance of health care workers to SARS-CoV-2 infection despite their high-risk work environment remains unclear. To investigate if inflammation and circadian disruption contribute to resistance or diminished susceptibility to the SARS-CoV-2 virus, we retrospectively evaluated a cohort of volunteer hospital nurses (VHNs). Methods: A total of 246 apparently healthy VHNs (mean age 37.4 ± 5.9 years) who had received the BNT162b2 mRNA vaccine were asked to report their sleep quality, according to the Pittsburgh Sleep Quality Index, and number of SARS-CoV-2 infections during the observational study period (from the end of December 2020 to April 2025). The expression of inflammation-associated mediators and circadian transcription factors in peripheral blood mononuclear cells, as well as sleep quality, were examined. Results: Our findings revealed no anthropometric, biochemical, or inflammation-associated parameters but demonstrated significantly greater levels of NFE2L2, also known as nuclear factor erythroid-derived 2-like 2 (NFR2), gene expression in peripheral blood mononuclear cells among VHNs who had never been infected with SARS-CoV-2 (n = 97) than in VHNs with only one (n = 119) or with two or more (n = 35) prior SARS-CoV-2 infections (p < 0.01). This result was confirmed through one-to-one propensity score matching (p < 0.01). Moreover, NRF2 gene expression was not associated with the number of COVID-19 vaccinations (p = 0.598). Finally, NRF2 gene expression was higher among participants who reported better sleep quality (p < 0.01). Conclusions: Our findings suggest possible interactions among NRF2 gene expression, protection against SARS-CoV-2 infection, and the modulation of COVID-19 vaccination efficacy.